Knowledge, attitude and readiness of Kuala Nerus primary school teachers in the implementation of stem in teaching and learning process - Che Seman, Shamilati; Wan Yusoff, Wan Mazwati; Mokhtar, Ahmad Shahrol; Che Seman, Nairul Nisah (Universiti Sultan Zainal Abidin, 2022)
Teachers are the most influential agents in implementing STEM as well as other changes to ensure the effectiveness of the new curriculum. For that reason, this study was conducted to identify the level of knowledge, attitude and readiness on STEM education and its implementation of primary school teachers who taught Science, Mathematics and RBT (Reka Bentuk dan Teknologi) in Kuala Nerus. It also sought to discover the relationship between teachers’ readiness and knowledge, attitude and experience. This quantitative study collected data using online survey method involving 110 respondents consisting of Science, Mathematics and RBT teachers randomly selected from the population of primary school teachers in Kuala Nerus, Terengganu. The result showed that the level of knowledge, attitude and readiness of the respondents were at a moderate level. However, there was a significant relationship with moderate strength between teachers’ readiness and knowledge; weak relationship between readiness and attitude; and strong negative relationship between readiness and teaching experiences. The findings enable schools to formulate appropriate strategies to strengthen the knowledge, skills,attitudes and confidence of the teachers in planning and delivering lessons of STEM education. The study concludes that knowledge and positive attitudes on STEM would help the teachers to deliver STEM education effectively. Moreover, by attending courses and practices continuously, they could gather experiences, enhance their teaching abilities and expose to the new innovation and changes in the education world.